Legal and Economic Aspects of Debt Securitisation with Involvement of Special Purpose Corporation - Szydło, Wojciech (University of Wroclaw. Faculty of Law, Administration & Economics, 2020)
Securitisation is an asset management method aimed at issuing securities based on a separate set of claims. With this method, private entities and public entities delivering public tasks can have access to investment financing or operational financial through the capital market, bypassing a credit risk. It is achieved by bringing to a swap of a package of claims due to the entity with cash raised through issuing securities (e.g., bonds) backed by the debt obligations (claims). The paper presents legal and economic rules for organising the debt securitisation process involving a special purpose commercial law company set up to issue securities, which, next to securitisation through a securitisation fund, is one of the two types of securitisation of claims governed by Polish law. This paper was written within the research project financed by the National Science Centre No. DEC-2013/08/A/HS5/00642.
Keywords: sekurytyzacja papierów wartościowych; spółka celowa; pojazd specjalnego przeznaczenia; fundusz sekurytyzacyjny; cesja wierzytelności; umowa o subpartycypację; papiery wartościowe; obligacje